MPLS (School Environment Learning Media) with the Google Site platform in the management of learning content, discussions, assignments, and assessments. - I Gusti Prahmana; Ratih Puspadini; Rozaq Habibi; Muhammad Gifary; Rika Oktavia (International Journal of Community Service Implementation, 2025)
One form of community service that can be done is by implementing technology-based learning media in the school environment. In this context, we focus on using the Google Site platform to manage learning content, discussions, assignments, and assessments at SMK Esa Prakarsa. Google Site offers several advantages that are relevant to the needs of SMK Esa Prakarsa. Google Site learning content management allows you to organize learning materials in a structured way in the form of easy-to-access web pages. Materials can be integrated with a variety of formats such as text, images, videos, and links to external sources. Discussions and collaboration integrations with Google Classroom and Google Meet allow for more interactive discussions and collaborations. Comment features and discussion forums can be implemented to increase student participation. Assignment collection and grading can be uploaded and collected digitally through Google Classroom, which integrates with Google Site. Assignment assessment can be done online with a transparent and efficient assessment feature. This program is in line with the concept of Independent Learning Independent Campus (MBKM) which encourages students to be involved in community service activities that have a real impact. The use of Google Site as a learning platform also supports Key Performance Indicators (KPIs) which emphasize innovation in learning and the use of information technology. The condition of the school of SMK Esa Prakarsa is a vocational high school that focuses on technology and industry. The school has a number of skill programs that prepare students to enter the workforce or continue their education to a higher level. However, challenges in learning management are still the main obstacles that hinder the teaching and learning process